Can athletes` reports of self-regulated learning distinguish deliberate practice from physical preparation activity? - Bartulovic, D.; Young, B. W.; McCardle, L.; Baker, J. (Journal of Sports Sciences, 2019)
Sustained persistence in deliberate practice (DP) could be aided by engagement in adaptive motivational and metacognitive types of self-regulated learning (SRL) processes. We examined relationships between SRL and each of DP and physical preparation (PP; e.g., cross-training) in supervised, unsupervised, social and non-social practice contexts. 272 individual-sport athletes (from city to international level; M sport activity = 13.54 hrs/wk; 200 males, ages 18-35) completed the Self-Regulation of Learning Self-Report Scale and reported weekly DP and PP amounts. We found contrasting results depending on specific SRL processes. Self-monitoring was related to DP (total, supervised, social conditions) but inversely related to PP. Effort was inversely related to supervised DP but positively associated with PP. Planning was associated with DP, and reflection and self-efficacy related to PP. We discuss the contrast between DP and PP, highlighting differences in the nature of these practice activities, and self-monitoring as a key SRL process for DP.